The derivation of sectoral and provincial implications from power sector scenarios using an integrated assessment model at Korean provincial level: GCAM-Korea - Jeon, Seungho; Roh, Minyoung; Kim, Suduk (Energy Strategy Reviews, 2021)
In South Korea, the 7th largest emitter in the world, many emissions reduction policies are implemented. The impact of the policies on the entire energy system at provincial level, however, has rarely been investigated. From this perspective, this paper provides geographically updated assessment of emissions reduction policies. This study adopts two opposite policies, a tax on coal-fired generation (Coal scenario) and a subsidy on PV generation (PV scenario). As an Integrated Assessment Model (IAM), GCAM-Korea, a version of GCAM with provincial level resolution of Korea, is applied in this study. GCAM-Korea can provide insights across provinces as well as sectors. Simulation results show that Coal scenario increases electricity price, while PV scenario decreases electricity price. With different conditions in each end-use sector, different responses are expected by this electricity price change. Industry sector, especially steel and iron manufacture industry, shows the most susceptible response to the electricity price change through substitution of electricity with coal. Under Coal scenario, higher electricity price causes larger coal consumption with smaller electricity consumption, while under PV scenario lower electricity price causes smaller coal consumption with larger electricity consumption. This inter sectoral impacts are directly transformed into inter provincial impacts. This transformation should be carefully handled, considering that the top five provinces accounted for 83 % of total industrial energy consumption in South Korea. Even though there is a large fraction of coal consumed in industry sector, the tax on coal has been imposed only on thermal coal under current energy price policy in Korea. A tax on industrial coal use as a whole could possibly buffer the negative impacts from non-taxed coal consumption in iron and steel industry. Further empirical examination is required to check the validity of this prediction from the model. Finally, the positive impact of emissions reduction by tax on coal fired generation, in turn, triggers negative externality on other provinces by causing more consumption of coal in industry sector. Even if this simulation results can not be quantified in terms of total amounts of benefit compared with total amounts of damages caused by this negative externality, the existence of distributional issue of emissions reduction at provincial level has been successfully demonstrated. GCAM-Korea is shown to capture the provincial level characteristics of energy system and it can be applied for the analysis of regional energy plan being conducted every 5 years by the Ministry of Trade, Industry and Energy, Korea.
Keywords: Coal fired generation; Electricity-consumption; Empirical examination; Industrial energy consumption; Integrated assessment models; Level characteristic; Manufacture industry; Negative externalities; Integrated assessment; Multi-sectoral analysis; Provincial-level analysis; South Korea